New species of cynipid inquilines of the genus Synergus (Hymenoptera: Cynipidae: Synergini) from the Eastern Palaearctic - Schwéger, Szabina; Melika, George; Tang, Chang-Ti; Bihari, Péter; Bozsó, Miklós; Stone, Graham N.; Nicholls, James A.; Pénzes, Zsolt (Zootaxa, 2015)
Eight new species of cynipid inquilines, Synergus abei Melika & Schwéger, S. belizinellus Schwéger & Melika, S. changtitangi Melika & Schwéger, S. formosanus Schwéger & Melika, S. ishikarii Melika & Schwéger, S. kawakamii Tang & Melika, S. khazani Melika & Schwéger and S. symbioticus Schwéger & Melika, from the Eastern Palaearctic are described. Descriptions, diagnoses, biology, and host associations for the new species and a key to all known Eastern Palaearctic Synergus species are given. All taxa are supported by morphological and molecular data. We discuss the status of all previously described Eastern Palaearctic Synergus species, and provide validation and synonymization of some species.